PENDIDIKAN YANG MEMERDEKAKAN: Model Inklusifitas Pembelajaran pada PKBM Puspita Abepantai di Jayapura - Lestari, Nining Puji; Arifin, Ayu Ulandari; Iha, Wandaruni; Rosadi, Asep (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2024)
This article discusses the concern of the community in Abepantai, Jayapura City, Papua Province, for the education of citizens, especially those who cannot access formal education. Using a qualitative approach, this research explores the organization of education at PKBM Puspita Abepantai through primary and secondary data. The results show that PKBM Puspita Abepantai not only provides formal education equivalency programs, but also special programs for adult learners, such as tire patchwork, electric welding, and woodcraft courses. These programs not only aim to improve technical skills, but also soft skills needed in the world of work and daily life. In addition, education at PKBM Puspita Abepantai is flexible and inclusive, emphasizing group, tutorial, and independent learning. Through this approach, PKBM Puspita Abepantai contributes to supporting equal access to education and empowering local communities.